A Cross-Sectional Study on Association between Metabolic Syndrome and Hepatobiliary Cancers - Muhammad Irfan Shehzad, Anwar Ul Haq, Ikram Zada, Muhammad Adnan Shahid, Noman Kareem Qureshi, Shah Bakht Azeem (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Several studies have supported the idea that a metabolic abnormality contributes to expansion of hepatocellular carcinoma (HCC). To date, metabolic factors have not been shown to be associated with hepatocellular carcinoma (HCC). Therefore, the present study aimed to assess the metabolic syndrome association with hepatocellular carcinoma. Patients and Methods: This cross-sectional study was carried out on surgically treated and radiologically confirmed 360 HCC cases in Gastroenterology Department of Central Hospital, Sargodha and Hayatabad Medical Complex Peshawar, during the period from January 2022 June 2022. Study protocol was approved by the research and ethical committee. Informed written consents were taken from each individual. Body mass index, blood pressure, medical history, and other related information were gathered from medical records. Patients were categorized into different groups based on their BMI: i) <18.5 kg/m2, ii) 18.5-23.9 kg/m2, iii) 24-29.9 kg/m2, Fiv) 30-34.9 kg/m2 and ≥ 35 kg/m2. A routine biochemical or immunological analytic method was used to determine all metabolic parameters and liver function tests. The metabolic-associated factors were associated with HCC-related different liver function’s test and stratified for BMI, free fatty acids, and Glycated Albumin (GA). Chemical analysis was used to detect antioxidant capacity (TAOC) and malondialdehyde (MDA). Data analysis was done in SPSS version 27. Results: Of the total 360 HCC patients, there were 234 (65%) male and 126 (35%) females. The overall mean age was 68.62±6.4 years. The association between hepatobiliary cancer and body mass index (BMI), smoking, ischemic heart disease, hypertension, and diabetes was found in a univariate analysis of the data. Based on BMI, patients were categorized as follows: 35 (9.7%) in (<18.5 kg/m2), 70 (19.4%) in (18.5-23.5 kg/m2), 118 (32.8%) in (24-29.9 kg/m2), 88 (24.4%) in (30-34.9 kg/m2), and 49 (13.7%) in (≥ 35 kg/m2). The incidence of smokers, non-smokers, and ex-smokers were 146 (40.6%), 60 (16.7%), and 154 (42.8%) respectively. The prevalence of different risk factors such as hypertension, diabetes, ischemic heart disease, Aspirin use, and statin use was 188 (52.2%), 124 (34.4%), 66 (18.3%), 148 (41.1%), and 142 (39.4%) respectively. The HCC group had significantly higher mean body mass index, glucose level, and lipid level than controls (P <0.05). HCC patients showed a significant association between liver function and metabolic factors. A significant association between high level of GA and increased cancer risk were found between cases and control. Conclusion: The present study concluded that hepatobiliary carcinoma may be caused by metabolic syndrome, which includes dyslipidemia, a high body mass index, and high serum glucose levels as independent risk factors. This finding supports previous research and emphasizes that the connection between hapotabiliatry cancer and increased BMI remains for liver tumors, bile duct cancer, and gallbladder cancers. Keywords: Hepatobiliary carcinoma, metabolic syndrome, Obesity, Diabetes